Space Imagination and Space Myths in Verbal Sources: Th e Case of Kronstadt - S. O. Savin (Сравнительная политика)
Th e article demonstrates the results of research of formed space myths in verbal sources by conducting polls and in-depth interviews with the citizens of Kronstadt town. Th ere is a diff usion of two space perceptions among the inhabitants: as an isolated fortress with its own temper and rules and as the suburbs of the big center. Given that the permanent connection with the “continent” has become possible quite recently, one can follow the dynamical infl uence of new transport routes on the myths and attributes of Kronstadt’s space.